2021
DOI: 10.1073/pnas.2024656118
|View full text |Cite
|
Sign up to set email alerts
|

A solution to a sex ratio puzzle in Melittobia wasps

Abstract: The puzzling sex ratio behavior of Melittobia wasps has long posed one of the greatest questions in the field of sex allocation. Laboratory experiments have found that, in contrast to the predictions of theory and the behavior of numerous other organisms, Melittobia females do not produce fewer female-biased offspring sex ratios when more females lay eggs on a patch. We solve this puzzle by showing that, in nature, females of Melittobia australica have a sophisticated sex ratio behavior, in which their strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 89 publications
1
12
0
Order By: Relevance
“…We would also expect that, due to limited mating capacity of adult males, the numbers of males in broods would increase gradually as brood sizes increase (as observed in this study and previously by Kapranas et al, 2016;Abdi et al, 2021). Until these possibilities are further evaluated, the extremely biased sex ratios exhibited by Sclerodermus constitute one of the remaining sex allocation puzzles among parasitoid hymenopterans (Abe et al, 2021). future studies will investigate foundress behaviour when provided with such options.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We would also expect that, due to limited mating capacity of adult males, the numbers of males in broods would increase gradually as brood sizes increase (as observed in this study and previously by Kapranas et al, 2016;Abdi et al, 2021). Until these possibilities are further evaluated, the extremely biased sex ratios exhibited by Sclerodermus constitute one of the remaining sex allocation puzzles among parasitoid hymenopterans (Abe et al, 2021). future studies will investigate foundress behaviour when provided with such options.…”
Section: Discussionmentioning
confidence: 99%
“…While formal modelling has recently supported this suggestion qualitatively (Iritani et al, 2021), the predicted reduction in brood sex ratios (an increase in female bias) is insufficient to provide a close match to observations, although it remains possible that refinement of the modelling assumptions employed may provide a better match. Other studies have tested for possible relationships between the kinship of Sclerodermus foundresses (either directly experimentally controlled or inferred from wing dimorphism) and sex ratio, since reproducing with close relative co-foundresses is predicted to select for female bias (Abe et al, 2021;Gardner & Hardy, 2020; see also Abdi et al, 2020c) but have found no effect (Abdi et al, 2020a(Abdi et al, , 2020b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Density-dependent dispersal has been observed across diverse taxa, from microbes to mammals [12,[33][34][35][36]. Empirical studies suggest that sex allocation can be shaped by population density and dispersal status [37][38][39], yet the possible role for density-dependent dispersal to modulate the evolution of sex allocation remains to be investigated empirically. Species with readily measurable dispersal and sex phenotypes, such as thrips [12,40], may provide opportunities for empirical testing.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, we simplified the models by removing non-significant factors ( α > 0.05) from the least-significant ones with a backward stepwise deletion procedure to arrive at a minimum adequate model [ 19 ]. We evaluated the statistical significance of the fixed effect using a likelihood ratio test to compare the change in deviance between the models [ 20 , 21 ]. To verify whether dermal suction changes joint ROM and SWV, we tested the difference between PRE and the other conditions.…”
Section: Methodsmentioning
confidence: 99%